INTERPRETATION OF COLOR AS AN ANTHROPOCENTRIC SUBSTANCE (TAMADDUN NURI JURNALI, 2024)
This article examines the formation and semantic features of such color designations as black, blue, brown, green, gray, orange, pink, purple, red, white, yellow, which are among the main color lexemes in modern English. The cognitive properties of color nomination are analyzed.